2017
DOI: 10.18632/oncotarget.15085
|View full text |Cite
|
Sign up to set email alerts
|

Designing of dual inhibitors for GSK-3β and CDK5: Virtual screening andin vitrobiological activities study

Abstract: Alzheimer's disease is a multifactorial neurodegenerative disorder with many drug targets contributing to its etiology. Despite the devastating effects of this disease, therapeutic methods for treating Alzheimer's disease remain limited. The multifactorial nature of Alzheimer's disease strongly supports a multi-target rationale as a drug design strategy. Glycogen synthase kinase-3 beta and cyclin-dependent kinase 5 have been identified as being involved in the pathological hyperphosphorylation of tau proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Interestingly, the efficacy of various antiepileptic drugs (AEDs) has been tested in epilepsy experimental models and in AD patients, showing a promising function in cognitive impairment prevention (Sánchez et al, 2018). Since tau hyperphosphorylation is the main mechanism responsible for NFT formation, it has been suggested that inhibiting different tau kinases such as CDK5 and GSK3β, involved in tau hyperphosphorylation, could reduce their aggregation (Xie et al, 2017;Holzer et al, 2018), observed in AD (Morris et al, 2011) and epilepsy (Sen et al, 2007;Thom et al, 2011;Tai et al, 2016).…”
Section: Therapeuticsmentioning
confidence: 99%
“…Interestingly, the efficacy of various antiepileptic drugs (AEDs) has been tested in epilepsy experimental models and in AD patients, showing a promising function in cognitive impairment prevention (Sánchez et al, 2018). Since tau hyperphosphorylation is the main mechanism responsible for NFT formation, it has been suggested that inhibiting different tau kinases such as CDK5 and GSK3β, involved in tau hyperphosphorylation, could reduce their aggregation (Xie et al, 2017;Holzer et al, 2018), observed in AD (Morris et al, 2011) and epilepsy (Sen et al, 2007;Thom et al, 2011;Tai et al, 2016).…”
Section: Therapeuticsmentioning
confidence: 99%
“…Recent studies utilized VS for AD drug screening for MTDLs that are intended to inhibit multiple associated targets. In this regard, two significant targets-GSK-3β and CDK5-were inhibited by means of sequential docking to screen compounds, whereas ligand-based virtual screening was performed in another study on inhibition of GSK-3β and BACE1 [190,191]. Nonetheless, recursive partitioning (RP) and NB, ML-based VS methods were used to screen compounds for MTDLs against AD.…”
Section: Ai-based Interventions In Advanced Therapeuticsmentioning
confidence: 99%
“…There exist numerous examples in the literature of the application of various types of machine learning classifiers for virtual screening [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Commonly used classifiers include naïve Bayes, k-nearest neighbors, support vector machines, random forests, and artificial neural networks (ANNs).…”
Section: Introductionmentioning
confidence: 99%